Utilização das equações de Navier Stokes com a parametrização convectiva BMJ para prognóstico de temperatura, umidade e vento sobre diferentes condições de estabilidade atmosférica utilizando o modelo regional ETA - Araújo, Janduy Guerra (2012)
Here an approach is made on the impact of convective parameterization Bettes - Miller - Janjic (BMJ) on temperature, moisture and wind predicted by the model ETA. There are several papers in the literature that focus on this topic, few directed in particular to the state of Paraiba, but none of them uses the methodology described herein. It is known that below the cloud base (850hPa) profiles of temperature and moisture are not affected by the BMJ parameterization scheme because it does not consider the downdrafts of cold air to lower levels. Given this assumption, the methodology implemented in this work is to compare temperature, moisture and wind series provided by ETA with the respective synoptic analyzes of convective ERA-INTERIM/ECMWF for two contrasting situations. The model was configured with a horizontal resolution of 12 km and 30 vertical levels, covering the northeastern Brazil and the adjacent Atlantic and the focus of analysis is for three cities in the state of Paraiba. The results revealed that the predicted temperature to Joao Pessoa was slightly underestimated for low levels, while for the other two cities the model significantly overestimated the temperature at 1000 mb and slightly underestimated in 900 and 800mb. The predictions of moisture and wind were considered satisfactory when compared with the Analysis, and the best results were found at low levels. There were no significant differences between the estimates in both contrasting situations.